Colonial Legacy and Development: Reflection on Nigeria’s Oil Dependency and Economic Resilience amidst the COVID-19 Pandemic - Adzraa Andira; Freya Harber (Jurnal Sentris, 2022)
This paper argues that the lack of economic diversification caused by colonial practices serves as the cause of Nigeria’s dependency towards the oil sector, hence exacerbating their economic condition amidst the COVID-19 pandemic. What began as colonialism with the British Empire has carried out into today’s day and age as Nigeria’s economic vulnerability and dependency on its oil industry. Despite previous experiences in facing crises due to fluctuating global oil markets, it is apparent that the sector of mining and quarrying –including oil– still holds a great proportion of Nigeria’s domestic revenue sources, despite attempts to diversify the country’s economic portfolio. It is clear that Nigeria’s lack of diversification of economic sources as a colonial legacy makes the country more vulnerable towards crisis, especially in the context of COVID-19. Nigeria’s dependency on Oil in the wake of post-colonialism offers a good example of the vulnerable nature of economies that lack diversification. Furthermore, this study uses literature findings as its main source of data. One can also see literature comparison of the concept regarding the impact of neo-colonial frameworks towards former colonies.